PENERAPAN KEPATUHAN HUKUM DAN GOOD CORPORATE GOVERNANCE SEBAGAI UPAYA MENINGKATAN KINERJA PERUSAHAAN - Desni Raspita; Mona Wulandari; Hendra Apriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
Legal compliance and Good Corporate Governance (GCG) represents sound corporate principles that must be applied in company management, solely to safeguard the company's interests in pursuit of its aims and objectives. These sound principles entail a balanced relationship among corporate organs, shareholders, and stakeholders; a clear division of duties, authority, and responsibilities among corporate organs in accordance with the company's structure; and operational mechanisms aligned with the Limited Liability Company Law and the company's Articles of Association—all implementing GCG based on the principles of transparency, fairness, and accountability. This study employs doctrinal legal research. The concrete application of GCG principles aims to benefit the company by: first, facilitating access to domestic and foreign investment; second, securing a lower cost of capital; third, enabling better decision-making to enhance economic performance; fourth, boosting stakeholder confidence and trust in the company; and fifth, protecting the board of directors and board of commissioners from legal claims. Factors such as patrimonialism, family capitalism, and crony capitalism must be carefully considered regarding the implementation of GCG in Indonesia. These obstacles can impact independence, monitoring, control, and operational mechanisms, ultimately affecting the company's performance.